IONOMETRIC METHODS FOR THE ANALYSIS AND DETERMINATION OF HEAVY METALS IN ENSURING FOOD SAFETY OF FOOD PRODUCTS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Ensuring food safety requires reliable monitoring of heavy metal contamination in food products, as excessive levels of toxic metals pose serious risks to human health. In recent years, increased industrial activity, intensive agriculture, and environmental pollution have contributed to the accumulation of heavy metals in food raw materials. This study focuses on the application of ionometric methods for the analysis and determination of heavy metal content in food products as part of an improved food safety control system.